Transverse Upper Vaginal Septum Obstructing Labor: A Case Report - Figen Türkçapar; Ayşegül Öksüzoğlu; Necati Hançerlioğlu; Mustafa Uğur; Nuri Danışman (Medical Network, 2012)
A transverse vaginal septum is a rare congenital anomaly of the reproductive tract thought to arise from defective canalization of the vagina. If located in the upper vagina, these septa are likely to be incomplete and asymptomatic. In the lower vagina they may be obstructive and found at the time of menarche, similar to an imperforate hymen. However, some women with incomplete septa will not be diagnosed until their first pregnancy. Here, we describe the management and outcomes of patient with transverse vaginal septa first diagnosed during pregnancy, and review the obstetric literature pertinent to this condition.